Pengaruh Sikap, Self-Efficacy dan Norma Subjektif Terhadap Intensi Berwirausaha Siswa SMKN 16 Jakarta - Mayya Choirunnisya; Ati Sumiati; Santi Susanti (Rifa'Institute, 2021)
This study aims to determine whether there is an influence between Entrepreneurial Attitudes, Self Efficacy, and Subjective Norms on Entrepreneurial Intentions in class XII students of SMKN 16 Central Jakarta. The population in this study were 210 class XII students of SMKN 16 Jakarta. The sampling technique used proportional stratified random sampling so that the sample obtained was 138 students. The data analysis technique used is multiple regression analysis. Based on the results of the study that partially showed that there was a positive and significant influence between entrepreneurial attitudes and entrepreneurial intentions, then self-efficacy had a positive and significant effect on entrepreneurial intentions and the subjective norm variable had a significant positive effect on the entrepreneurial intention variable. Simultaneously shows that entrepreneurial attitudes, self-efficacy, and subjective norms affect entrepreneurial intentions. The results of this study indicate that the magnitude of the influence of the variables of entrepreneurial attitude, self-efficacy, and subjective norms has a contribution of 57.7% to entrepreneurial intentions, while the remaining 42.3% can be described by other variables not examined by researchers.